An assessment of morphometric and molecular variation in Monodelphis dimidiata (Wagner, 1847) (Didelphimorphia: Didelphidae) - Vilela, Júlio Fernando; Russo, Claudia Augusta De Moraes; de Oliveira, João Alves (Zootaxa, 2010)
This study aims to clarify the taxonomic status of Monodelphis dimidiata and M. sorex, using molecular and morphometric data. Cytochrome-b sequences were obtained from specimens morphologically assignable to those taxa from the vicinity of type localities, but also representing their presumptive area of sympatry and extremes in their known distributions. These sequences were compared to GenBank downloaded sequences of select Monodelphis spp. and also of Marmosa lepida, Micoureus demerarae, and Didelphis albiventris, used as outgroups. Genetic distances and maximum likelihood analyses were performed to recover phylogenetic affinities among taxa. To access morphometric variation, univariate and multivariate statistical methods (Principal Component Analysis and Canonical Variate Analysis) were applied to the covariance matrix of 25 craniometric measurements obtained from a total of 108 specimens sampled across the geographic ranges of the species. The molecular analyses revealed a clade composed by haplotypes assignable to Monodelphis dimidiata and M. sorex (sensu Pine and Handley 2007) as distinct from the remaining Monodelphis species sampled to date, with 100% bootstrap support. Within this clade, one haplotype from Itatiaia was the sister clade to the remaining 11 specimens from Montevideo (Uruguay), Rio Grande do Sul and Santa Catarina states (Brazil), which formed an assemblage without clear geographic arrangement. In the morphometric analyses, the first two principal components of morphometric data separated variables associated with general latent size comparably expressed in all samples, and a group of variables including molars widths, molar toothrow length, and postorbital constriction breadth, which separates the geographic samples in a sequence coincident, to a large extent, with their latitudinal distributions. The sample from Itatiaia, Rio de Janeiro State, was again revealed as clearly distinct from the remaining samples, suggesting that it may represent a peripheral isolated population. With the study of original descriptions and published information on the type material of M. sorex, including photographs of syntypes, our analyses point to the recognition of M. sorex as a subjective junior synonym of M. dimidiata, which is then regarded as a widespread taxon ranging from the latitudes of southern Buenos Aires Province and Córdoba in Argentina to at least Minas Gerais State in southeastern Brazil, through the Pampas and the Atlantic Forest domains.